The Effect of Jigsaw Type Cooperative Learning Model on Students Learning Outcomes In Social Studies Subjects: Case Study of SMP Reformasi Makassar, Indonesia - Jinna, J.; Nurdin, N.; Iskandar, Andi Arifuddin; Syarifuddin, S. (Manunggal Halim Jaya, 2024)
This study aims to: (1) provide an overview of the results of the analysis of learning tools for Social Studies (IPS), (2) provide an overview of the analysis of the Jigsaw-type cooperative learning model, and (3) determine the effect of the Jigsaw-type cooperative learning model on social studies learning outcomes of class VIII students at SMP Reformasi Makassar. This research is descriptive quantitative in nature. The population consists of all class VIII students, totaling 30, with a saturated sampling technique, meaning that the population equals the sample size of 30 students. The research location is SMP Reformasi Makassar, and a quantitative approach was used. Data collection techniques include written tests in the form of essay questions, observation, and documentation. Data analysis involved descriptive analysis, hypothesis testing (paired sample test), and validity and correlation tests. The results of the analysis of learning tools in this study indicate that, in general, they are valid, practical, and effective. The analysis of the Jigsaw-type cooperative learning model shows that it can: (a) improve cognitive learning outcomes, (b) increase student interest in learning Social Studies, (c) help students understand the learning material more quickly, and (d) encourage cooperation among students in understanding the material. The use of the Jigsaw-type cooperative model can also increase the level of student achievement. The probability value of X is < 0.01. The calculated t-value of 6.313 is greater than the estimated t-value of 2.045 (n-1 = 29, alpha 5%). Thus, it can be concluded that the Jigsaw-type cooperative learning model has a significant effect on the learning outcomes of class VIII students at SMP Reformasi Makassar.